2008
DOI: 10.1364/ao.47.004501
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid digital holographic imaging system for three-dimensional dense particle field measurement

Abstract: To apply digital holography to the measurement of three-dimensional dense particle fields in large facilities, we have developed a hybrid digital holographic particle-imaging system. The technique combines the advantages of off-axis (side) scattering in suppressing speckle noise and on-axis (in-line) recording in lowering the digital sensor resolution requirement. A camera lens is attached to the digital sensor to compensate for the weak object wave from side scattering over a large recording distance. A simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…For holograms that cover a larger volume at a lower magnification, Meng and colleagues (Cao et al 2008, Salazar et al 2008 reduce the DOF by using a hybrid setup, which still involves in-line holography, but records 90 • side scattering from particles (Figure 4c). Ooms et al (2006) have introduced another approach, which inserts a ring-shaped circular aperture between a pair of identical lenses, which are separated by twice their focal length.…”
Section: Tracking and Measurements Of Particle Displacement From Digimentioning
confidence: 99%
See 2 more Smart Citations
“…For holograms that cover a larger volume at a lower magnification, Meng and colleagues (Cao et al 2008, Salazar et al 2008 reduce the DOF by using a hybrid setup, which still involves in-line holography, but records 90 • side scattering from particles (Figure 4c). Ooms et al (2006) have introduced another approach, which inserts a ring-shaped circular aperture between a pair of identical lenses, which are separated by twice their focal length.…”
Section: Tracking and Measurements Of Particle Displacement From Digimentioning
confidence: 99%
“…Results supported the view that the generation of hairpins was governed by the base-flow shear strain and the existence of a sufficiently large initial disturbance. Recently, Cao et al (2008) and Salazar et al (2008) used the setup shown in Figure 4c to measure the spatial distribution of particles in isotropic turbulence and compared the results with DNS predictions. The experiments were performed in a special isotropic turbulence facility containing air, and consisted of measuring the location of several hundred 6-μm hollow glass spheres in a 1-cm 3 volume.…”
Section: Applications Related To Turbulence Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the extended DOF, DH is now gaining as an emerging and promising characterization tool in many scientific and engineering fields. DH has been successfully applied in the numerous fields such as micro-structure testing [27], investigation of red blood cell [28], in spray analysis [29], microscopy [30][31][32], bubble characterization [33], particle characterization [34][35][36][37], particle image velocimetry (PIV) [38], and biological applications [39][40]. In spite of these advantages, DH has inferior qualities in terms of pixel resolution and image dimension [25].…”
Section: Background and Motivationmentioning
confidence: 99%
“…As a result, DH will take off as a widely embraced tool for particle characterization at the time of its transition from transmission to the reflection mode. So far, some literature has been found out in which 90 0 scattering of the object wave front was captured by the digital sensors [25,36]. No literature is reported about the reflection based digital particle holography.…”
Section: Directions For Future Researchmentioning
confidence: 99%